Călin Ioan DUȘE, Imperiul Roman și creștinismul în secolul I [The Roman Empire and Christianity in the 1ˢᵗ Century], Cluj-Napoca, Cluj University Press, 2023, 836 p. - Marius TELEA (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica)
The work of Father University Lecturer, Dr. Călin Ioan Dușe, bearing the title The Roman Empire and Christianity in the 1st Century, is part of the author’s concern to highlight the connection between the Roman Empire and the establishment of Christianity in the world. Christianity spread mainly due to the conditions offered by the Roman Empire, and those who preached the new teaching in the first centuries of the Christian era benefited from the protection offered by the Roman administration, but also by the infrastructure of the Empire.